EKSISTENSI KRIYA KULIT TARUMPAH DI BIDO COLLECTION KELURAHAN SAMBONG JAYA KECAMATAN MANGKUBUMI KOTA TASIKMALAYA - Rafli Rustan Nawawi, Muhammad; Husen, Wan Ridwan; Apriani, Arni (Jurnal Seni dan Pembelajaran, 2023)
Tarumpah is a typical Tasikmalaya leather craft. One of the manufacturers that produces this tarumpah leather craft is the Bido Collection Company which started producing tarumpah from 1997, with innovative and modern style models as well as strong and durable resistance, this makes the tarumpah produced by the Bido Collection unique. The research method used is qualitative research with an analytical descriptive. The results of this study say that the history of tarumpah is divided into 3 periods, namely the Hindu and Buddhist periods of the 9th century to the 13th century, the Islamic period of the 15th century to 1930, and the period after independence in 1950-2000. The process of making the first tarumpah leather patterning and cutting, secondly painting, thirdly leather rubbing and re-patterning, fourthly giving motifs, sizes and brands, fifthly upper fitting, sixth fitting of soles, seventh sewing, eighth sanding and finishing. Tarumpah regeneration at the Bido Collection occurred in 2015 and 2018 because many craftsmen left and needed craftsmen for production. Craftsmen training in Bido is carried out for 3 months. The method used is the drill or repetition method.Keywords: Leather Craft, Tarumpah, Bido Collection.